Is It Time We Stop Discouraging Evening Physical Activity? New Real-World Evidence From 150,000 Nights - Kahn, Michal; Korhonen, Topi; Leinonen, Leena; Martinmaki, Kaisu; Kuula, Liisa; Pesonen, Anu-Katriina; Gradisar, Michael (Frontiers in Public Health, 2021)
Professional and colloquial sleep hygiene guidelines advise against evening physical activity, despite meta-analyses of laboratory studies concluding that evening exercise does not impair sleep. This study is the first to investigate the association between objectively measured evening physical activity and sleep within a real-world big-data sample. A total of 153,154 nights from 12,638 individuals aged 18-60 years (M=40.1 SD=10.1; 44.5% female) were analyzed. Nighttime sleep and minutes of physical activity were assessed using Polar wearable devices for 14 consecutive days. Thirty mins or more of moderate-to-near maximal physical activity during the 3 h before sleep onset were recorded in 12.4% of evenings, and were more frequent on weekdays compared to weekends (13.3% vs 10.2% respectively, p < 0.001). Linear mixed modelling revealed that sleep efficiency was not significantly associated with evening physical activity, and that sleep duration was 3.4 mins longer on average on nights following evenings in which participants engaged in 30 mins or more of moderate-intense physical activity. Effects were found for sleep timing metrics, as evening physical activity was linked with earlier sleep onset and offset times (–13.7 and –9.3 mins, respectively). Overall, these effects were greater– but still very small– on weekdays compared to weekends. The present study provides further evidence for the lack of meaningful links between sleep duration or quality and physical activity in the hours preceding sleep. Taken together with recent meta-analytic findings, these findings suggest that changes in public health recommendations are warranted regarding evening physical activity and its relation to sleep.